Occupational eye health and productivity loss: The impact of photokeratitis among electric welders in Gowa, Indonesia - Syahrir, Ria Anggraeni; Israr, Muhammad (Sociality: Journal of Public Health Service, 2025)
Occupational eye disorders, particularly photokeratitis, have received limited attention in developing regions, despite their significant impact on worker productivity. This study aimed to assess the relationship between photokeratitis symptoms and work productivity among electric welders in Gowa Regency, Indonesia. Employing an observational design with a cross-sectional approach, data were collected from 63 electric welders across 14 welding workshops in Samata Subdistrict, Somba Opu District. The presence of photokeratitis symptoms and productivity levels were assessed through structured interviews and categorized accordingly. Statistical analysis using the chi-square test (α=0.05) revealed that 75.0% of respondents with photokeratitis symptoms were less productive, while only 25.0% remained productive. Conversely, among those without symptoms, 87.0% were productive, and 13.0% were less productive. The association between photokeratitis and productivity was statistically significant (p=0.001; OR=20.000). These findings underscore the critical role of occupational eye health in sustaining productivity in rural industrial settings. Public health interventions, including the promotion of personal protective equipment and workplace safety education, are imperative to mitigate productivity loss among welders.